Exploring Molecular Spectroscopy: Insights into Chemical Structures and Interaction - Neha Sahu (International Journal of Photochemistry and Photochemical Research, 2024)
A key tool for understanding the dynamics, structure, and interactions of molecules is molecular spectroscopy. This abstract outlines the key principles and techniques employed in modern molecular spectroscopy, highlighting its significance in various scientific disciplines. The focus is on the principles of absorption, emission, and scattering of electromagnetic radiation by molecules, leading to valuable insights into molecular properties. The abstract begins by discussing the basic principles of molecular spectroscopy, emphasizing how molecules interact with light and how these interactions provide information about molecular structure, composition, and environment a brief introduction is given to various spectroscopic techniques, such as Raman spectroscopy, nuclear magnetic resonance (NMR), infrared (IR), and ultraviolet-visible (UV-Vis). Furthermore, the abstract explores the importance of molecular spectroscopy in fields such as chemistry, physics, biology, and materials science. A brief introduction is given to various spectroscopic techniques, such as Raman spectroscopy, nuclear magnetic resonance (NMR), infrared (IR), and ultraviolet-visible (UV-Vis). The abstract also addresses recent advancements in molecular spectroscopy, including the development of novel techniques and instrumentation that enable higher sensitivity, resolution, and versatility in molecular analysis. These advancements have expanded the capabilities of spectroscopy in studying complex molecular systems and dynamic processes. In conclusion, molecular spectroscopy continues to be a cornerstone of modern scientific research, providing powerful tools for characterizing molecules at the atomic and molecular levels. Its applications span a wide range of disciplines and continue to evolve with technological innovations, promising further insights into the intricate world of molecules and materials.
Keywords: Spectroscopy; absorption; electromagnetic radiation; molecular structures; molecules absorb light